Action of Water in Depressing Acetylene Reduction by Detached Nodules - Van Straten, J. (1975)
Adverse effects of water on acetylene reduction by detached soybean root nodules could not be attributed to ethanol formation, but apparently were associated with nodule tissue damage caused by detachment. Intact nodules were not affected by moisture.